2021
DOI: 10.1111/dme.14711
|View full text |Cite
|
Sign up to set email alerts
|

The use of mice in diabetes research: The impact of physiological characteristics, choice of model and husbandry practices

Abstract: Diabetes mellitus is characterised by hyperglycaemia, which results from an absolute or relative lack of insulin. Chronic and acute hyperglycaemia are associated with a range of health complications and an overall increased risk of mortality. Mouse models are vital in understanding the pathogenesis of this disease and its complications, as well as for developing new diabetes therapeutics. However, for experimental questions to be suitably tested, it is critical that factors inherent to the animal model are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 115 publications
1
22
0
Order By: Relevance
“…24 Overall, these results highlight the role of welfare in scientific outcomes and the importance of consistency in practices and full disclosure of methods. 4.1.2 | Moving animals from holding rooms to procedure rooms In many animal units, mice are transported from holding rooms to procedure rooms prior to experimentation (e.g., GTTs). Conversely, because CGM requires mice to remain on their receiver mats for measurements to be taken, mice remain in their holding room for procedures.…”
Section: Fastingmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Overall, these results highlight the role of welfare in scientific outcomes and the importance of consistency in practices and full disclosure of methods. 4.1.2 | Moving animals from holding rooms to procedure rooms In many animal units, mice are transported from holding rooms to procedure rooms prior to experimentation (e.g., GTTs). Conversely, because CGM requires mice to remain on their receiver mats for measurements to be taken, mice remain in their holding room for procedures.…”
Section: Fastingmentioning
confidence: 99%
“…3 However, many common preclinical end points in diabetes research can be impacted by the strain, sex and model of mouse chosen and so this should be carefully considered when planning in vivo experiments. 4 The choice of end points and protocols are also vital in experimental design to ensure that data are reproducible and translatable. 5 Indeed, it has been shown that poor study planning and implementation has direct implications on clinical translatability.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models are useful for identifying and testing novel therapeutic strategies that could translate into a better protection against human disease. The diabetogenic diet-fed C57BL/6 diabetic mice model has been widely used in DN research, and these mice are particularly susceptible to HFD-induced type 2 diabetes [ 17 ]. The HFD hyperinsulinemic db/db mice model displays a substantial glomerular pathology, including a mesangial matrix expansion and modest albuminuria [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Streptozotocin is a Streptomyces chromogen-derived broad-spectrum antibacterial and anti-neoplastic nitrosourea derivative. It is a potent alkylating agent that has been shown to affect glucose transfer and glucokinase action and induce many DNA strand breaks [12]. Diabetes in mice may be caused by a single large dose of streptozotocin, most likely due to direct harmful effects.…”
Section: Animal Models and Type 1 And 2 Modelsmentioning
confidence: 99%